COFFEE PRODUCTION IN THE SOUTH OF MINAS PLANNING REGION AND IN NEPOMUCENO, MINAS GERAIS - Vilas Boas, Lucas Guedes (Geosaberes, 2020)
Coffee production is one of the main economic activities in southern Minas Gerais. Several aspects favored its dissemination in the the south-Minas Gerais municipalities, including in Nepomuceno. The article discusses the recent situation of coffee growing in Nepomuceno and in the planning region of Southern Minas, in which the municipality is located. Bibliographic research, document analysis, fieldwork and semi-structured interviews were the methodological procedures adopted. The majority of local and regional coffee growers from sell their production to agricultural Cooperatives. Furthermore, temporary work during coffee harvesting is common in the south of Minas and in Nepomuceno. Although the cultivation of specialty and/or organic coffees has grown in recent years in Brazilian territory and in some southern Minas Gerais municipalities, its production is still incipient in Nepomuceno.